Comparison and political strategy: Internationalism, colonial rule and urban research after Fanon. (June 2022) - Kipfer, Stefan
Debates about comparative method have been at the forefront of English-language urban studies during the last two decades. In one sense, these debates simply derive from and help sustain the crucial labour process of urban research. In other respects, the rise of comparative method to foremost prominence has demonstrated theoretical differences in the field. The heat that some of these debates have occasionally generated (e.g. on scale, global cities, assemblage and planetary urbanisation) alerts us to the political stakes involved in comparison. These range from the micro-political dynamics of knowledge creation to various macrological considerations. In this paper, I deal not only with the political implications of comparative projects, I also raise the question: how do political strategies produce comparative perspectives? After a few observations about comparative debates in urban research and beyond, I zero in on Frantz Fanon's tricontinental internationalism as a generator of a relational comparative outlook before discussing three intellectual engagements with Fanon's legacy. These engagements are situated within the creole literary movement in Martinique, Indigenous radicalism in Canada and political anti-racism in mainland France. By highlighting the obstacles that stand in the way of translating Fanon's internationalism, these engagements also underline the importance of understanding colonial rule and its legacies (including its urban dimension, which Fanon understood under the larger rubric of colonial compartmentalisation) in relationally comparative ways: historically and geographically distinct but inter-linked through broader processes, strategies and intellectual practices.